2012
DOI: 10.1158/1541-7786.mcr-11-0206
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Androgen Receptor, Lipogenesis, and Oxidative Stress Converged by SREBP-1 Is Responsible for Regulating Growth and Progression of Prostate Cancer Cells

Abstract: We previously reported that sterol regulatory element-binding protein-1 (SREBP-1) is involved in the transcriptional regulation of androgen receptor (AR) and formation of fatty acid through altered expression of fatty acid synthase (FASN). In this communication, we provide a new finding that SREBP-1 induced oxidative stress in prostate cancer cells through increased production of reactive oxygen species (ROS) and expression of NADPH oxidase 5 (Nox5). We have shown that: 1) Expression of SREBP-1 protein is posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
184
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(191 citation statements)
references
References 46 publications
7
184
0
Order By: Relevance
“…Furthermore, Huang et al, (2011) reported that overexpression of SREBP-1 increased ROS content in prostate cancer cells [37]. These findings further support our results.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Furthermore, Huang et al, (2011) reported that overexpression of SREBP-1 increased ROS content in prostate cancer cells [37]. These findings further support our results.…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Furthermore, we believe that the combined effect of both the DHT inhibition and the activation of AMPK caused a reduction in the expression of FASN in the group treated with a combination of dutasteride and metformin. This effect may be facilitated by the reduced expression in SREBP-1, which has recently been shown to regulate expression of AR [24]. This recent study by Huang et al showed that by genetically overexpressing or knocking down SREBP-1 in LNCaP cells resulted in a corresponding increase or decrease in AR expression [24].…”
Section: Discussionmentioning
confidence: 98%
“…This effect may be facilitated by the reduced expression in SREBP-1, which has recently been shown to regulate expression of AR [24]. This recent study by Huang et al showed that by genetically overexpressing or knocking down SREBP-1 in LNCaP cells resulted in a corresponding increase or decrease in AR expression [24]. Our data confirms the above reported findings where the greatest reduction in AR and PSA expression was seen with a combination group of dutasteride and metformin, with a corresponding reduction of SREBP-1.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, significant levels of NOX5 have been reported in PC-3 human prostate cancer cells. Detection of NOX5 in PC-3 cells coupled with the observation that NOX5 expression is upregulated by sterol regulatory element-binding protein-1 both in vitro and in vivo in the context of prostate cancer progression, does implicate a proliferative role for NOX5 in prostate cancer (54). There have been two other detailed studies of NOX5 in the context of tumor biology; in 2005, the expression of NOX5 in hairy cell leukemia was reported to regulate constitutive phosphorylation signals mediating proliferation, and in 2006, acidinduced NOX5-S expression was reported to contribute to increased cell proliferation and decreased apoptosis in Barrett's esophageal adenocarcinoma cells (38,61).…”
mentioning
confidence: 98%